Handbook on European Union Climate Change Policy and Politics - Rayner, Tim; Szulecki, Kacper; J. Jordan, Andrew; Oberthür, Sebastian (Edward Elgar Publishing, 2023)
Through detailed and wide-ranging analysis, the Handbook on European Union Climate Change Policy and Politics provides a critical assessment of current and emerging challenges facing the EU in committing to and delivering increasingly ambitious climate policy objectives. Highlighting the importance of topics such as finance and investment, litigation, 'hard to abate' sectors and negative emissions, it offers an up-to-date exploration of the complexities of climate politics and policy making.